1992
DOI: 10.1126/science.255.5045.695
|View full text |Cite
|
Sign up to set email alerts
|

Deformational Mass Transport and Invasive Processes in Soil Evolution

Abstract: Soils are differentiated vertically by coupled chemical, mechanical, and biological transport processes. Soil properties vary with depth, depending on the subsurface stresses, the extent of mixing, and the balance between mass removal in solution or suspension and mass accumulation near the surface. Channels left by decayed roots and burrowing animals allow organic and inorganic detritus and precipitates to move through the soil from above. Accumulation occurs at depths where small pores restrict further passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
0
11

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(197 citation statements)
references
References 22 publications
(10 reference statements)
4
182
0
11
Order By: Relevance
“…For example, researchers have suggested that trees can set (i) the frequency with which soils are overturned and moved downslope by tree throw (Lutz and Griswold, 1939;Schaetzl and Follmer, 1990;Norman et al, 1995), (ii) the extent and magnitude of soil expansion through root network propagation (Brimhall et al, 1992;Hoffman and Anderson, 2014), and (iii) the persistence of soil-stabilizing root networks (Denny and Goodlett, 1956;Schaetzl and Follmer, 1990;Norman et al, 1995). In most erosional settings, the depth of mobile soil, h, coincides with the depth of physical or biological disturbance processes (Roering et al, 2010;Yoo et al, 2011).…”
Section: Architectural Layering Of the Critical Zonementioning
confidence: 99%
“…For example, researchers have suggested that trees can set (i) the frequency with which soils are overturned and moved downslope by tree throw (Lutz and Griswold, 1939;Schaetzl and Follmer, 1990;Norman et al, 1995), (ii) the extent and magnitude of soil expansion through root network propagation (Brimhall et al, 1992;Hoffman and Anderson, 2014), and (iii) the persistence of soil-stabilizing root networks (Denny and Goodlett, 1956;Schaetzl and Follmer, 1990;Norman et al, 1995). In most erosional settings, the depth of mobile soil, h, coincides with the depth of physical or biological disturbance processes (Roering et al, 2010;Yoo et al, 2011).…”
Section: Architectural Layering Of the Critical Zonementioning
confidence: 99%
“…Estes processos no perfi l de alteração podem ter causado o enriquecimento residual e/ou relativo de argilas oxídicas (óxidos e hidróxidos de ferro), além de titânio. Considerando o Ti como elemento de referência (potencialmente imóvel) e normalizando em função de seu teor na rocha, conforme Brimhall et al., (1991) verifi ca-se uma perda signifi cativa de todos os elementos analisados neste trabalho, mesmo de Fe e Al se comparado com a rocha considerada parental, exceto para o VAI 5Bt4, mas isso pode se dever a um teor muito baixo de Ti nesse material (Figura 4).…”
Section: Análise Pedogeoquímica Do Perfi L De Alteraçãounclassified
“…Determinar a mobilidade geoquímica que ocorre durante o intemperismo pode ajudar a estabelecer uma sequên-cia de alteração em determinado ambiente no manto estudado. Diversos trabalhos foram realizados com o objetivo de determinar a mobilidade de elementos químicos durante o processo de alteração das rochas e formação dos solos (RUXTON, 1968;COLMAN, 1982;HUDSON, 1988;BRIMHALL et al., 1991;HODSON et al., 1996;ANDERSON et al., 2002;HODSON et al., 2002;PRICE & VEBEL, 2003;LASHERAS ADOT et al., 2006;HASKINS, 2006 (CHAPMAN et al., 1991). Dentro deste contexto, o presente trabalho tem como objetivo analisar um manto de alteração nas suas característi-cas laterais, assim como, a análise pedogeoquímica de um perfi l representativo neste manto de alteração localizado na porção noroeste da caldeira vulcânica de Poços de Caldas (MG).…”
Section: Introdução E Objetivounclassified
“…Bu denklemde;M j,flux (z w ),horizondaki element hareketliliğini (gcm -2 ) g değerinin pozitif olması sisteme katılımı, negatif olması sistemden kayıp o Hacimsel değişim hesaplamalarında Ti, toprak ortamında düşük hareke element olarak kullanılmıştır (Marshall &Haseman 1942;Brimhall&Dietri 1990;Brimhall et al 1991a;Merritts et al1992 (Fedo et al 1995) ( 1) Burada; ε i,w, standardize edilmiş hacimsel değişim katsayısı; Δz w , horizon kalınlığı (m); Δz, profil kalınlığı (m), değerin pozitif çıkması kazanımları gösterirken negatif değer ise yıkanmayı ya da kayıpları gösterir.…”
Section: Kütle Dengesiunclassified
“…Bu denklemde;M j,flux (z w ),horizondaki element hareketliliğini (gcm -2 ) g değerinin pozitif olması sisteme katılımı, negatif olması sistemden kayıp o Hacimsel değişim hesaplamalarında Ti, toprak ortamında düşük hareke element olarak kullanılmıştır (Marshall &Haseman 1942;Brimhall&Dietri 1990;Brimhall et al 1991a;Merritts et al1992 Profil içerisindeki elementlerin hareketliliği ise aşağıda verilen denklemle s…”
Section: Kütle Dengesiunclassified